2005
DOI: 10.1007/s11136-004-3061-3
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and health utility for the institutional elderly in Taiwan

Abstract: Results indicate that the WHOQOL-BREF, excepting the sexual activity item, is useful for evaluating HRQOL of conscious elderly in institutions. The validity of TTO utility for studying the institutionalized elderly needs further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
32
3
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 31 publications
13
32
3
2
Order By: Relevance
“…In addition, item 21 (sexual life) in the WHOQOL-BREF (TV) exhibited a high missing value for Taiwanese-speaking elderly. The high missing response rate on item 21 was consistent with the findings of the WHOQOL-BREF Mandarin Chinese version [22,23] and might be due to a substantial proportion of elderly people living alone (e.g., 92% in this study). It could also be that Chinese/Taiwanese culture discourages explicit self expression of such sexual desires [22,23].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, item 21 (sexual life) in the WHOQOL-BREF (TV) exhibited a high missing value for Taiwanese-speaking elderly. The high missing response rate on item 21 was consistent with the findings of the WHOQOL-BREF Mandarin Chinese version [22,23] and might be due to a substantial proportion of elderly people living alone (e.g., 92% in this study). It could also be that Chinese/Taiwanese culture discourages explicit self expression of such sexual desires [22,23].…”
Section: Discussionsupporting
confidence: 87%
“…The high missing response rate on item 21 was consistent with the findings of the WHOQOL-BREF Mandarin Chinese version [22,23] and might be due to a substantial proportion of elderly people living alone (e.g., 92% in this study). It could also be that Chinese/Taiwanese culture discourages explicit self expression of such sexual desires [22,23]. Hwang et al [23] and Power et al [21] have suggested that considering intimacy other than sexual intercourse might increase the response from the elderly on this item.…”
Section: Discussionsupporting
confidence: 87%
“…The most commonly used variables were age, race, education level, and chronic health conditions. 51,53 in Sweden, two (7.40%) 42,57 in Spain, and one (3.70%) each in China, 43 Portugal, 47 England, 59 and Australia. 40 Of these 27 studies, only one (3.70%) 47 used a direct measure of PA (accelerometer).…”
Section: Characteristics Of the Longitudinal (Cohort) Studiesmentioning
confidence: 99%
“…In these studies, the International Physical Activity Questionnaire (IPAQ) 2,54,56,58,60,62,63 and Physical Activity Scale for the Elderly (PASE) 35,36,38,46,55 were the most frequently used instruments (24.13 and 17.24%, respectively) for estimating PA participation. Three studies (10.34%) 35,36,50 used a test battery of functional fitness, and two studies (6.89%) 43,48 used functional capacity self-assessment Box 1 Instruments used to assess physical activity and quality of life in the studies included in the review (instruments listed by acronym; see full names in a footnote to the Supplementary Table online) Physical activity -Accelerometer: measures minutes and counts per day in moderate and vigorous physical activity. -Andersen's behavioral model: in this model, contextual and individual characteristics are conceptualized as factors that impede or enhance the individual's health behaviors, most notably health care utilization and subsequent other outcomes related to health and satisfaction.…”
Section: Evaluation Of Pa and Qolmentioning
confidence: 99%
“…In consultation with the WHOQOL-BREF's developers, it was reworded in order to retain its usefulness within the social relationships domain as: 'How satisfied are you with the support you get from your family?'. The replaced item was rated the least important in a cross-cultural validation study [46] and had elicited a poor response rate amongst a group of institutional elderly [47] and older adults in Norway and Canada [48]. The altered question was retained for the LBC1936.…”
Section: Quality Of Lifementioning
confidence: 99%